Characteristics of Pediatric Intensive Care Patients Following the 2020 İzmir Earthquake - Eşe Eda Turanlı; Pınar Yazıcı Özkaya; Gülizar Koç; İrem Ersayoğlu; Bülent Karapınar (Galenos Yayinevi, 2023)
Aim: Unforeseeable disasters such as earthquakes can lead to significant catastrophes. Early and effective treatment methods are life-saving in reducing post-earthquake mortality and morbidity. The aim of this study was to evaluate the treatment and outcomes of patients with crush injuries in the Izmir earthquake. Materials and Methods: Eight patients, 2 male, and 6 female were admitted to the intensive care unit. The medical records of these 8 crush injury patients were retrospectively reviewed. Results: Eight children rescued from rubble were admitted to the pediatric intensive care unit, and one of them died. The median age of the patients was 148.5 (range, 35 to 210) months and the median PRISM score was 4 (interquartile range 0-31). The median duration of being trapped under the rubble was 23 (range: 4 to 92) hours. Conclusion: Crush syndrome is a life-threatening event. The authors believe that early transportation and immediate intensive care therapy would have improved survival rates.